Retraction Notice - -, - (Jurnal Riset Teknik Sipil dan Sains, 2024)
Retraction notice to ”Evaluasi Kinerja Ruas Jalan Raya Panjang Jiwo Permai Akibat Pembangunan Rumah Sakit Ubaya Kota Surabaya” [Jurnal Riset Teknik Sipil dan Sains, vol.2, no.1, 2023, pp. 18-23] Salfa Hanum Cahyani1, Kurnia Hadi Putra2 1,2 Institut Teknologi Adhi Tama Surabaya This article has been retracted. The authors have plagiarized part of a paper that had already appeared in ETNIK : Jurnal Ekonomi dan Teknik Vol.2, No.8, Year 2023 in Indonesian Language and available online at https://etnik.rifainstitute.com/index.php/etnik/article/view/238. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.